PEMETAAN DAYA DUKUNG TANAH UNTUK PONDASI DANGKAL DI WILAYAH PESISIR PANTAI KOTA BENGKULU - Samsul Bahri; Makmun R. Razali; Kendar Aryadi Elsandy (Universitas Bengkulu, 2019)
This research aims to analyze the capacity of resources support the land and give information to the public about the value of the power capacity of the soil to support a shallow Foundation in the area of the coast of the city of Bengkulu. This research analyzes the power capacity in support of land the formula Meyerhoft. The data used in the form of the data of sondir, physical soil test and deploy as many as 100 questionnaire respondents. The results of the questionnaire show that the widely used building Foundation community is kind of shallow Foundation with this type of Foundation is constantly mates stone times. The dimensions of the foundation gained as much as 8 type with the dominant dimension, namely 20/40 cm and 50 cm high with a total of as much as 28%. The sieve analysis test results show that land on the coast is poorlygraded sand, gravel sand, with little fine grain. The value of the smallest land grant support power worth 0.875 kg/cm2 with dimensions Foundation 30/50 cm high 40 cm in Kelurahan of Malabero. The value of the power of the highest land grant support totaling 5.358 kg/cm2 with the dimensions of the Foundation 20/40 cm height 50 cm in Kelurahan of Lempuing. Based on the results of the analysis of the soil indicate that support power rating power support land grant still capable to shoulder the burden of building on it. The value of the resource support land grant obtained from the sondir data value is equal to the value soil permit support power conversion results to SPT.